2020
DOI: 10.1093/rheumatology/keaa463
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, outcome and management of patients with SLE and secondary antiphospholipid antibody syndrome after aPL seroconversion

Abstract: Objective The withdrawal of oral anticoagulation (OAC) in patients with SLE and secondary aPL syndrome (SAPS) who become seronegative has not been clearly investigated to date. Our aim was to evaluate the prevalence of aPL seroconversion and the prognosis of SLE patients with SAPS who withdrew OAC after aPL negativization. Methods We retrospectively analysed data of all SLE patients (ACR criteria) with SAPS (Sydney criteria) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…However, the proportion of patients in our cohort who remained persistently LA positive (72%) was similar to the rates in other studies that used different definitions of LA stability and positivity (78% in the study by Gkrouzman et al, 71% in the study by Zen et al, and 87% in study by Erkan et al). 9,10,36 Finally, we only analyzed the effect of the first negative test on future events. We did not compare patients who became transiently LA negative to patients who became persistently negative, as the number of those latter patients was very low (only 14/42 patients remained persistently negative).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the proportion of patients in our cohort who remained persistently LA positive (72%) was similar to the rates in other studies that used different definitions of LA stability and positivity (78% in the study by Gkrouzman et al, 71% in the study by Zen et al, and 87% in study by Erkan et al). 9,10,36 Finally, we only analyzed the effect of the first negative test on future events. We did not compare patients who became transiently LA negative to patients who became persistently negative, as the number of those latter patients was very low (only 14/42 patients remained persistently negative).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports of safe discontinuation of anticoagulation in patients with APS who became persistently negative for aPL and our analysis cannot be applied to these patients. 10,37 However, these studies also included patients with only aCL or aβ2GPI, which are regarded as weaker risk factor for thrombosis. 35,[38][39][40] Similar to findings by Khawaja et al and Zen et al 10,29 , we found that the majority of patients who had a negative LA test subsequently had at least one additional positive test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The titers of aPL frequently decrease and eventually become negative during the follow-up period [29]. The negativization has been related to a lower risk of thrombotic event, allowing to discontinuation of anticoagulation after aPL seroconversion seems to be reasonably safe, at least in primary APS [30].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“… 73 Indeed, thrombotic events frequently occur in the setting of antiphospholipid antibody syndrome (APS), whose prevalence in SLE is estimated to be around 30%. 74 76 Noteworthy, recurrent episodes of VTE may lead to chronic thromboembolic pulmonary disease and, eventually, pulmonary arterial hypertension (PAH). Therapy of pulmonary thromboembolism is mainly based on anti-coagulants.…”
Section: Pulmonary Involvement In Slementioning
confidence: 99%